Severe Acute Respiratory Syndrome Coronavirus 2 Viremia Is Associated With Coronavirus Disease 2019 Severity and Predicts Clinical Outcomes. (10th August 2021) - Jacobs, Jana L; Bain, William; Naqvi, Asma; Staines, Brittany; Castanha, Priscila M S; Yang, Haopu; Boltz, Valerie F; Barratt-Boyes, Simon; Marques, Ernesto T A; Mitchell, Stephanie L; Methé, Barbara; Olonisakin, Tolani F; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral RNA (vRNA) is detected in the bloodstream of some patients with coronavirus disease 2019 (COVID-19), but it is not clear whether this RNAemia reflects viremia (ie, virus particles) and how it relates to host immune responses and outcomes. Methods: SARS-CoV-2 vRNA was quantified in plasma samples from observational cohorts of 51 COVID-19 patients including 9 outpatients, 19 hospitalized (non–intensive care unit [ICU]), and 23 ICU patients. vRNA levels were compared with cross-sectional indices of COVID-19 severity and prospective clinical outcomes. We used multiple imaging methods to visualize virions in plasma. Results: SARS-CoV-2 vRNA was detected in plasma of 100%, 52.6%, and 11.1% of ICU, non-ICU, and outpatients, respectively. Virions were detected in plasma pellets using electron tomography and immunostaining. Plasma vRNA levels were significantly higher in ICU > non-ICU > outpatients ( P < .0001); for inpatients, plasma vRNA levels were strongly associated with higher World Health Organization (WHO) score at admission ( P = .01), maximum WHO score ( P = .002), and discharge disposition ( P = .004). A plasma vRNA level >6000 copies/mL was strongly associated with mortality (hazard ratio, 10.7). Levels of vRNA were significantly associated with several inflammatory biomarkers ( P < .01) but not with plasma neutralizing antibody titers ( P = .8). Conclusions: Visualization of virus particles in plasma indicates that SARS-CoV-2 RNAemia is due, at least in part, to viremia. The levels of SARS-CoV-2 RNAemia correlate strongly with disease severity, patient outcome, and specific inflammatory biomarkers but not with neutralizing antibody titers. Abstract : Plasma viral RNA was detected in most hospitalized coronavirus disease 2019 patients including all critically ill patients, and the levels of RNA are strongly associated with disease outcome. SARS-CoV-2 virions were identified in plasma using multiple complementary approaches.